2017
DOI: 10.1038/emm.2017.199
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin–pyrroloquinoline formulation prevents hypertrophy–induced pathological damage by relieving mitochondrial stress in cardiomyocytes under hypoxic conditions

Abstract: This study investigates the therapeutic effect of a nanocurcumin formulation (NCF) containing nanocurcumin (NC) and pyrroloquinoline quinone (PQQ) on ameliorating hypoxia-induced stress in hypertrophied primary human ventricular cardiomyocytes (HVCM) under hypoxic conditions, as validated in a Sprague-Dawley rat model of chronic hypobaric hypoxia (cHH)-induced right ventricular hypertrophy (RVH). Based on our previous findings, here, we analyzed the improvement in the protective efficacy of NCF against mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The above-mentioned results indicate that the effects of PQQ on protecting the heart from ischemia/reperfusion injury may be accomplished by its ability to scavenge free radicals to protect the mitochondria from oxidative stress. In addition, it has been reported that the nanocurcumin-PQQ formulation prevents hypertrophy-induced pathological damage by relieving mitochondrial stress in cardiomyocytes under hypoxic conditions, while under these conditions, PQQ treatment alone can improve cellular viability (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above-mentioned results indicate that the effects of PQQ on protecting the heart from ischemia/reperfusion injury may be accomplished by its ability to scavenge free radicals to protect the mitochondria from oxidative stress. In addition, it has been reported that the nanocurcumin-PQQ formulation prevents hypertrophy-induced pathological damage by relieving mitochondrial stress in cardiomyocytes under hypoxic conditions, while under these conditions, PQQ treatment alone can improve cellular viability (19).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that PQQ can modulate the number and function of the mitochondria in mice, and can directly react with reactive oxygen species (ROS) in the mitochondria to maintain the dynamic balance of ROS (16). However, to date, at least to the best of our knowledge, there are only few reports on the effects of PQQ on cardiac hypertrophy (17)(18)(19)(20)(21). Based on previous studies (17)(18)(19)(20)(21), it was hypothesized that PQQ may be protective against Iso-induced cardiac hypertrophy.…”
Section: Pyrroloquinoline Quinone Attenuates Isoproterenol Hydrochlormentioning
confidence: 99%
See 1 more Smart Citation
“…On a global scale, various alternative strategies are evaluated for cardio‐protective attributes. It is in general consensus that employment of natural bioactive materials promotes homeostasis and/or protection under stress/challenge with minimal untoward effects . In this regards, traditional Chinese medicines shares a long history of high repute and may plausibly lay the foundation for better therapeutic interventions for cardiovascular ailments including hypertrophy .…”
Section: Discussionmentioning
confidence: 99%
“…The same authors then used formulations combined with nanocurcumin and pyrroloquinoline, a polyphenolic compound found in kiwi fruits, to study their effect against mitochondrial damage. The formulation showed a higher potency in modulating cardiac hypertrophy than nanocurcumin or pyrroloquinoline alone [113]. Recently, an in-vivo study showed magnetic hydrogel nanocomposite loaded with curcumin that was able to show a cardioprotective effect against toxicity induced by doxorubicin.…”
Section: Cardioprotective Effectmentioning
confidence: 99%